EXPERIENCED VS NOVICE EFL TEACHERS: A STUDY OF SPEAKING ASSESSMENT LITERACY - Cansu Aykut Kolay; Büşra Ulu (Language Literacy: Journal of Linguistics, Literature, and Language Teaching)
Assessment is a core component of foreign language education, significantly influencing teaching and learning processes. Since various skills, including reading, writing, listening, speaking, and grammar, must be assessed separately, language teachers need to be assessment literate in each skill. Among these, Language Assessment Literacy (LAL) is critical for effective teaching. While numerous studies have explored teachers' assessment literacy for reading, writing, listening, and grammar, limited research focuses on speaking assessment literacy. This study addresses this gap by examining the speaking assessment literacy of novice and experienced teachers. Using a qualitative research design, data were collected from 16 EFL teachers (eight novice and eight experienced) through nine semi-structured interview questions adapted from established question repositories. Thematic analysis was employed to examine the data across three aspects: knowledge, beliefs, and practices. The findings highlighted differences and similarities between the two groups. While experienced and novice teachers shared common speaking assessment practices, differences emerged in their overall levels of speaking assessment literacy. The results underscore the need for tailored pre-service and in-service training programs focusing on skill-based language assessment. These programs should be integrated into teacher education and induction to enhance assessment competence across varying levels of teaching experience. This study contributes to the understanding of speaking assessment literacy, offering insights for improving teacher training in foreign language education.